Design and Optimization for Simulated Moving Bed: Varicol Approach. Issue 3 (2021) - Matos, Joana; Faria, Rui P.V.; Loureiro, José M.; Ribeiro, Ana M.; Nogueira, Idelfonso B.R.
Abstract: Simulated Moving bed adsorption processes are characterized by their complex dynamic behavior. Due to this issue, as deeper are explored their design possibilities, more complexity is expected. One example of this is the Varicol configuration. In this operating mode, it is possible to use more than one configuration in two consecutive switches through an asynchronous switch, reducing the unit costs in comparison with standard configurations. This work presents a new strategy for the design and concomitant optimization of SMB devices considering a Varicol operating mode. The optimization will include both the operating conditions and the configuration of the device. The optimization results enable the design of a Varicol configuration for the separation of the bi-naphthol enantiomers which can also be generelazied for other systems. The results have shown that including the configuration in the optimization process allows to increase the productivity of the separation process by 15% while reducing the total unit size.